2008
DOI: 10.4028/www.scientific.net/amr.55-57.27
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoparticles as Smart Heating Mediator for Hyperthermia and Sorbent Regeneration

Abstract: Titanium oxide (TiO2) nanopowders can be reproducibly formed by hydroxylation of titanium organic complexes. The crystallisation to anatase and rutile can be controlled by systematic calcination and a complex range of properties optimized for specific applications. Characterisation of the powders has been undertaken using advanced physical techniques. The morphology of the TiO2 powders is determined by solution concentration and precipitation phenomena, particularly temperature and stirring regime. However the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…A size of 50 nm or 500 nm was claimed to be necessary to observe in nanomanganites the same behaviour as in bulk La-Ca or La-Sr systems, respectively. 17,20 In contrast, other authors reported, for x close to 0.3 for both La-Ca and La-Sr systems, an increase of T C with cristallite size 10,22,25 that would be correlated to the lattice distortions at the grain surface, which caused a structure relaxation from the surface to the core of the grain. 10 The formation of magnetic polarons was also proposed as a possible cause for such a T C increase.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…A size of 50 nm or 500 nm was claimed to be necessary to observe in nanomanganites the same behaviour as in bulk La-Ca or La-Sr systems, respectively. 17,20 In contrast, other authors reported, for x close to 0.3 for both La-Ca and La-Sr systems, an increase of T C with cristallite size 10,22,25 that would be correlated to the lattice distortions at the grain surface, which caused a structure relaxation from the surface to the core of the grain. 10 The formation of magnetic polarons was also proposed as a possible cause for such a T C increase.…”
Section: Introductionmentioning
confidence: 79%
“…17,20 In contrast, other authors reported, for x close to 0.3 for both La-Ca and La-Sr systems, an increase of T C with cristallite size 10,22,25 that would be correlated to the lattice distortions at the grain surface, which caused a structure relaxation from the surface to the core of the grain. 10 The formation of magnetic polarons was also proposed as a possible cause for such a T C increase. Dutta et al also reported a T C increase in La 0.875 Sr 0.125 MnO 3 nanoparticles that was fully consistent with the increased symmetry observed in this case.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…12 Few papers dealt with magnetic suspensions based on LSMO or unaggregated LSMO nanoparticles, and some of them were specific for MFH application. [16][17][18][19][20][21] These nanoparticles were prepared by several routes: the freeze drying technique, 13,14 coprecipitation, 15 Pechini route, [16][17][18] microwave refluxing technique, 19 and conventional solid-state reactions followed by mechanical milling. 20,21 Nevertheless, each of these techniques necessitate an extra stage of calcination at a temperature over 700 C in order to get well-crystallized compounds.…”
Section: Introductionmentioning
confidence: 99%
“…However, remnant bridges were often maintained leading to the formation of submicrometric aggregates of nanocrystallites. [13][14][15][16][17][18][19][20][21] That is why we investigated another route based on the Glycine Nitrate Process (GNP). Among self-combustion synthesis routes, GNP was firstly proposed in 1990 by Chick et al to elaborate chromite and manganite powders.…”
Section: Introductionmentioning
confidence: 99%